The Impact of Hyperbaric Oxygen Therapy on Serum C-Reactive Protein Levels, Osteoprotegerin Expression, and Osteoclast Numbers in Induced-Periodontitis Diabetic Rats - Mulawarmanti, Dian; Parisihni, Kristanti; Widyastuti, Widyastuti (European Journal of Dentistry, 2020)
Objectives This study aimed to examine the impact of hyperbaric oxygen therapy (HBOT) on serum C-reactive protein (CRP) levels, osteoclast numbers, and osteoprotegerin (OPG) expression in periodontitis-induced diabetic ratsMaterials and Methods This study constituted an in vivo laboratory-based experiment incorporating a posttest only control group design. Thirty male Wistar rats were divided into three groups of research subjects: a healthy group (K0), periodontitis-induced diabetic group (K1), and periodontitis-induced diabetic group treated with HBOT for 7 days (K2). After treatment, the subjects were sacrificed to determine the level of serum CRP by the ELISA method. Immunohistochemical analysis was conducted to check the level of OPG expression, while a histological analysis was undertaken to quantify the number of osteoclasts.Statistical Analysis The data was analyzed using a one-way ANOVA and Least Significant Difference (LSD) test on which a result of p < 0.05 was considered statistically significant.Results HBOT appreciably decreased serum CRP levels, significantly enhancing OPG expression in periodontitis-induced diabetic (p < 0.05) and decreasing the number of osteoclasts in -periodontitis-induced diabetic (p > 0.05).Conclusion HBOT reduced the serum CRP level, increased OPG expression, and decreased osteoclast numbers in periodontitis-induced diabetic rats.
Keywords: C-reactive protein; osteoprotegerin; osteoclast; diabetes mellitus; periodontitis